2010
DOI: 10.2478/v10022-010-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ultrasonic Methods in the Identification of Honey Types

Abstract: The objective of this study was to determine the correlations between the viscosity and temperature of honey and the velocity of ultrasonic wave propagation, and to investigate the use of ultrasonic methods in the identification of different honey types. Within the analyzed temperature range, a significant correlation was found between ultrasound propagation velocity and the viscosity of honey. The results of this experiment suggest that the velocity of ultrasonic wave propagation measured at a temperature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…For instance, Singh et al [14] were able to prove adulterations of honey using the speed of ultrasound passing through honey samples. These kinds of parameters have also been used recently to distinguish honeys at different temperatures [15,16]. González-Mohino et al [17] used ultrasound attenuation to characterize different varieties of honey.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Singh et al [14] were able to prove adulterations of honey using the speed of ultrasound passing through honey samples. These kinds of parameters have also been used recently to distinguish honeys at different temperatures [15,16]. González-Mohino et al [17] used ultrasound attenuation to characterize different varieties of honey.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasounds have been successfully applied to identify turkey meat and pork (Nowak, 2015) Novoa-Dìaz et al ( 2014) proposed an ultrasonic method for monitoring red wine ageing (Tempranillo, Spain). Ratajski et al (2013) demonstrated the applicability of ultrasound testing for identifying selected types of honey (rapeseed and mixed flower honey). Ultrasonic measurements were also successfully deployed to test the ripeness of Cheddar and Mahón cheese (Benedito et al, 2002) as well as Manchego cheese (Benedito et al, 2005)…”
Section: Type Of Beermentioning
confidence: 99%

A Non-destructive Method for Identyfing Beers

Wesołowski,
Jadwisieńczak,
Wesołowski
et al. 2023
Preprint
“…Propagation of ultrasonic waves through honey helps to determine its adulteration because mixing of adulterants will changes its physical properties such as density, viscosity and homogeneity etc., these properties have direct impact on the velocity of ultrasonic waves through the medium. Ultrasonic methods were used by Ratajski et al [8] to identify honey types. The ultrasonic velocity can be used with other properties, results in many important thermodynamic properties [9].…”
Section: Introductionmentioning
confidence: 99%